PEMANFAATAN TEKNOLOGI PEMBANGKIT LISTRIK HYBRID PADA PETERNAKAN AYAM DESA SUKONOLO KABUPATEN MALANG - Arianto, Rangga; Wijaya, Afif Sulton; Dudik, Zainal; Sirojuddin, Mohammad; Arista, Prima (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Our lives are now so dependent on electricity. Loss of electricity could cause our lives could not walk normally. Various aspects of life becomes blocked, either from our daily lives to efforts that require electrical energy. The high cost of electricity tariff barriers add to the long facing entrepreneurs. Chicken farm is one of the types of businesses that require a constant electrical energy, in case of rolling blackouts it will directly affect the production process. In addition, the location of the chicken farm that is usually placed at distant places, also very influential on the continuous supply of electrical energy. Hybrid power plant technology is the right solution to respond all these problems. The plant can harness the energy that is around us, such as wind and sunlight. Then make it a stable supply of electrical energy, constant, and environment friendly. Hybrid plant is capable of producing electrical energy 12 kWh / day while the partner needs to reach 5.31 kWh / day and a chicken farmer can save electricity cost of Rp. 173,600 / month. With the results of the application of Hybrid Generating proven to reduce production costs by utilizing renewable energy on a chicken farm village Sukonolo Malang, so that energy independence can be achieved.Keywords: Electrical energy, chicken farms, hybrid power plants.